A FITTED METHOD FOR SINGULARLY PERTURBED DIFFERENTIALDIFFERENCE EQUATIONS HAVING BOUNDARY LAYERS VIA DEVIATING ARGUMENT AND INTERPOLATION. (2020) - SINGH, RAGHVENDRA PRATAP; REDDY, Y. N.
No abstract available